DEVELOPMENT STRATEGY OF HONEY BEE FARMING BUSINESS USING THE SOAR APPROACH AT KTH PEMATANG TUNGKUNG IN KELAGIAN VILLAGE - Marwoto Marwoto; Rince Muryunika; Febrian Hutagalung (Universitas Muhammadiyah Palembang, 2026)
Honey bee farming is one form of non-timber forest product utilization that has economic potential to be developed. This study aimed to analyze the development strategy of honey bee farming in Kelagian Village, Tebing Tinggi District, Tanjung Jabung Barat Regency. The research was conducted in December 2025 using survey and interview methods involving 6 honey bee farmers as respondents. Data analysis was carried out using the SOAR approach through the preparation of IFAS, EFAS, and strategic matrices. The results showed that the number of honey hive locations increased from 4 locations in 2020 to 24 locations in 2024. The IFAS analysis obtained a score of 3.62 and the EFAS analysis obtained a score of 3.87, indicating that the business development strategy was positioned in the Strengths–Results (SR) quadrant with the highest strategy value of 4.22. Based on these findings, the business development strategy was directed toward optimizing the group’s internal strengths, such as the availability of natural feed, infrastructure support, and group cohesiveness to improve production, marketing, and the sustainability of honey bee farming businesses.